A case of multiple dental anomalies: a variant of Ekman-Westborg-Julin trait - Colakoglu, Gizem; Kazak, Magrur; Buyukbayram, Isil Kaya; Elcin, Mehmet Ali; Bedeloglu, Elcin (My University)
Simultaneous occurrence of multiple dental anomalies is relatively common and has been reported particularly in cases with systemic alterations or syndromes. However, in 1974, Ekman-Westborg and Julin described a unique case of multiple macrodontia and multituberculism of posterior teeth accompanied by multiple dental malformations without other systemic anomalies. Here we report the case of a 20-year-old female patient who presented with macrodontia affecting her maxillary lateral teeth, mandibular incisors, and impacted multituberculated wisdom teeth accompanied by other dental anomalies that manifested itself as a variant of the Ekman-Westborg-Julin trait.
Keywords: Multituberculism; macrodontia; dental anomaly; Ekman-Westborg-Julin; cone-beam computed tomography